Strength and conditioning for sports performance (Routledge, 2016)
Part 1: Coaching 1. Effective coaching in strength and conditioning - the foundations of the profession (Dave Collins and Jeremy Moody) Part 2: Scientific basis of training 2. The structure and function of the neuromuscular system (Ian Jeffreys) 3. The biomechanical principles underpinning strength and conditioning (Jon E. Goodwin and Daniel J. Cleather) 4. The bioenergetics of sports performance (James P. Morton and Graeme L. Close) 5. Cardiorespiratory control of exercise and adaptation to training (Fred J. DiMenna and Andrew M. Jones) 6. The endocrine responses to training (Duncan N. French) 7. Nutrition for human performance (Graeme L. Close and James P. Morton) Part 3: Strength and conditioning - applied practice 8. Effective needs analysis and functional training principles (Steven S. Plisk) 9. Performance diagnostics (Jeremy M. Sheppard and Tim J. Gabbett) 10. Screening methods for the strength and conditioning practitioner (Raphael Brandon) 11. Developing strength and power (Michael H. Stone, Prue Cormie, Hugh Lamont and Meg Stone) 12. Weightlifting for sports performance (Clive Brewer and Mike Favre) 13. Plyometric training - theory and practice (Jon E. Goodwin and Ian Jeffreys) 14. Developing speed and agility for sports performance (Ian Jeffreys and Jon E. Goodwin) 15. Developing endurance for sports performance (Fred J. DiMenna and Andrew M. Jones) 16. Flexibility - developing effective movement (William A. Sands and Jeni R. McNeal) 17. The essentials of periodization (G. Gregory Haff) Part 4: Special considerations in strength and conditioning 18. Thinking sensibly about recovery (William A. Sands) 19. Paediatric strength and conditioning (Avery D. Faigenbaum and Fernando Naclerio) 20. Working with special populations (Mark Jarvis and Jeremy Moody) 21. Performing in extreme environments (Charles Pedlar and Greg Whyte) 22. Facility design, maintenance, safety issues and record keeping (John H. Taylor) Part 5: Sport-specific strength and conditioning 23. Strength and conditioning for football (Gary J. Walker) 24. Strength and conditioning for cricket (Huw Bevan) 25. Strength and conditioning for golf (Liam Hennessy) 26. Strength and conditioning for rowing (Alex Wolf) 27. Strength and conditioning for field hockey (Andy Hudson) 28. Strength and conditioning for basketball (John H. Taylor) 29. Strength and conditioning for tennis (Narelle Sibte) 30. Strength and conditioning for cycling (Martin Evans) 31. Strength and conditioning for track and field - throws (Meg Stone)